OPTIMASI PEMANFAATAN SISTEM PEMOMPAAN TENAGA ANGIN(SPTA) UNTUK SUMBER-SUMBER AIR DALAM DENGAN TURBIN ANGIN LISTRIK SUDU MAJEMUK SEBAGAI PENGGERAK POMPA - Pakpahan, Sahat; Soeripno (BRIN Publishing, 2003)
The application of WInd Energy Conversion Systems (WECS) for supplying water for households, irrigation, livestock or other purposes have been developed to increase the contribution of renewable source of energy to support people, particularly at locations where accessibility to public utility networks not available or when the system itself needed by the consumer. Various WECS available in market as well as commercial pumps which can be used for bored hole., deep well or surface water and must be matched for optimal performance of the whole system; therefore, the analysis for selection of a pump due to its design characteristics for matching with an existing wind turbine that result-in optimal conditions of supply and demand has to be performed. A wind turbine with 6 blades rotor installed at BBUG samas Bantul is taken as a case study.